Exploring Bourgeoisie Dynamics through Coriolanus Snow’s Character: A Comparative Study of The Hunger Games: The Ballad of Songbirds and Snakes Book and Movie Adaptation: Mengeksplorasi Dinamika Borjuis melalui Karakter Coriolanus Snow: Studi Komparatif antara Buku dan Film “The Hunger Games: The Ballad of Songbirds and Snakes” - Fatmarani, Widiasih; Melyana, Shafanda Putri; Rochmah, Devy Puspita Nor; Meyrasyawati, Dewi; Afdholy, Nadya (Journal of Literature and Education, 2025)
This study aims to examine the dynamics of the bourgeoisie through the character of Coriolanus Snow in Suzanne Collins’ The Hunger Games: The Ballad of Songbirds and Snakes and its film adaptation. Utilizing a qualitative comparative method, the research applies Marxist social class theory to analyze how Snow’s character reflects and critiques bourgeois ideologies in both the novel and the movie. The data were collected through textual and cinematic analysis, focusing on Snow’s socio-economic background, interactions, and personal transformation. The study highlights how internal narration in the novel and visual representation in the film construct different emphases on class struggle, power ambition, and ideological control. The findings reveal substantial differences in character development and thematic focus, illustrating how literature and film uniquely represent class hierarchies within a dystopian society.